Design and simulation of silicon-based magnetic sensor - Nor Azlan Mohamed (School of Microelectronic Engineering, University Malaysia Perlis, 2011)
In this thesis, the design and simulation of Silicon-Based Magnetic sensor is discussed. The transistor can be converting into a magnetic sensor by splitting drain structure of the conventional MOS transistor into two symmetrical parts. This work focused a research of new simple and compact model of split-drain MOSFET structures including geometrical effect of the devices and biasing dependency on the sensitivity. The key parameter is the Hall Effect, which indicates the current line deviation due to Lorentz force acting on the charge carriers. The magnetic sensor structures has been designed and simulated by using TCAD software, MEDICI and DAVINCI which aimed to identify an optimized design of magnetic sensor. The results of the study are presented in this work.